Reconfigurable circuits and technologies for smart millimeter-wave systems - Ferrari, Philippe; Jakoby, Rolf; Karabey, Onur Hamza; Maune, Holger; Rehder, Gustavo Pamplona (Cambridge University Press, 2022)
Get up to speed on the modelling, design, technologies, and applications of tunable circuits and reconfigurable mm-wave systems. Coverage includes smart antennas and frequency-agile RF components, as well as a detailed comparison of three key technologies for the design of tunable mm-wave circuits: CMOS, RF MEMS, and microwave liquid crystals, and measurement results of state-of-the-art prototypes. Numerous examples of tunable circuits and systems are included that can be practically implemented for the reader's own needs. Ideal for graduate students studying RF/microwave engineering, and researchers and engineers involved in circuit and system design for new communication platforms such as mm-wave 5G and beyond, high-throughput satellites in GSO, and future satellite constellations in MEO/LEO, as well as for automotive radars, security and biomedical mm-wave systems.